2021
DOI: 10.1007/s00402-021-04140-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite-coated compaction short stem represents a characteristic pattern of peri-prosthetic bone remodelling after total hip arthroplasty

Abstract: Purpose: We aimed to investigate the differences in peri-prosthetic bone remodelling between the full hydroxyapatite (HA)-collared compaction short stem and the short tapered-wedge stem.Methods: This retrospective cohort study enrolled 159 consecutive patients (159 joints) undergoing total hip arthroplasty (THA) using the full HA compaction short (n=64) and short tapered-wedge (n=95) stems. Body mass index (BMI), peri-prosthetic bone mineral density (BMD), and clinical factors, including the Japanese Orthopaed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We demonstrated that the mean value of stem valgus was significantly higher in the stem collar-calcar contact group than in the non-contact group, and the result can explain the reason for stem alignment changes to valgus during bone compaction in the stem collar-calcar contact group. However, we previously reported a relationship between the stem collar and periprosthetic BMD changes, and no differences was found in any of the Gruen zones between the stem collar-calcar contact and non-contact groups [ 5 ]. These findings supported our current result that stem alignment does not affect peri-prosthetic bone remodeling in the HA compaction stem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that the mean value of stem valgus was significantly higher in the stem collar-calcar contact group than in the non-contact group, and the result can explain the reason for stem alignment changes to valgus during bone compaction in the stem collar-calcar contact group. However, we previously reported a relationship between the stem collar and periprosthetic BMD changes, and no differences was found in any of the Gruen zones between the stem collar-calcar contact and non-contact groups [ 5 ]. These findings supported our current result that stem alignment does not affect peri-prosthetic bone remodeling in the HA compaction stem.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the influence of the proximal femoral canal shape on post-operative BMD changes in the femur [ 5 , 22 ]. The pre-operative femoral canal’s morphology did not affect the BMD at two years post-operatively around the Zweymüller-type stem [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation